Review of the genus Hongkongia (Araneae: Gnaphosidae) from China - Zhang, Feng; Zhu, Ming-Sheng; Tso, I-Min (Zootaxa, 2009)
The spider genus Hongkongia Song et Zhu, 1998, belonging to the Echemus group, is reviewed. A new species, Hongkongia songi sp. nov., is described, and the type species, Hongkongia wuae Song et Zhu, 1998 is redescribed.